C02 Emissions and Economic Growth: A Panel Data Analysis Evidence from Developing African Countries - Suleiman Saad; Yusuf Isa; Musa Muhammed; Baba Ali Usman (European Scientific Journal, ESJ, 2023)
This paper tests the Environmental Kuznet Hypothesis using data from 23 African countries for the period 1980–2019   in the Pedroni approach to panel cointegration analysis. The evidence suggests that both real GDP and energy consumption have a substantial effect on CO2 emission in most countries studied though energy consumption has less effect. However, in most countries, as income increases, the level of emission declines consistently with the EKC hypothesis. However, the econometric result, their interpretation, and their likely policy implications have to be taken with caution since there is a high degree of heterogeneity among the countries in terms of energy consumption,  real income as well as  CO2 emissions. This is more so when the analysis of the trend in the growth of the three variables used in estimation and the estimated results of fully modified OLS show large divergence among countries. However, the study recommends that, since a great number of economies in the study buttressed the EKC, therefore, the current policy on growth and energy consumption may be pursued without necessarily affecting the quality of their environment. However, other countries should implement strong regulatory and market-based policies on highly energy-intensive sectors to reduce their current level of emissions and attain sustainable, environment-friendly growth.